Psychological intervention and its immune effect in cancer patients: A meta-analysis. Issue 38 (September 2019) - Zhang, Ping; Mo, Lin; Li, Xia; Wang, Qiyao
Abstract: Objective: To determine whether psychological intervention (PI) changes the levels of immune indicators in cancer patients. Methods: We conducted a systematic search published up to July 2018, followed by a manual search. Randomized controlled trials were included. Two reviewers independently screened and extracted data, which were analyzed using Review manager 5.3. Results: Twenty-nine studies were included including four kinds of PI. Only stress management didn't result in immune changes; only cognitive behavior therapy affect NK cell activity. PI did not change immune indicators on cancer patients who completed therapy. Compared to patients not receiving PI, those received PI had significantly higher NK cell count and activity in whole blood; and serum levels of IL-2, IL-4, IFN-γ, lgA, and lgG. However, the differences in the serum levels of IL-6, IL-10, TNF-α, and IgM were not significant ( P  > .05), and the changes recorded for the CD3 +, CD4 +, and CD8 + cell count, and CD4 + /CD8 + ratios were inconsistent. Conclusions: Although there are considerable evidences of PI's immune effect, but its magnitude was moderate. Therefore, it may be premature to conclude whether PI affects immunity of cancer patients. Further research is warranted, with special focus on the PI types and treatment methods.